Genotoxicity, cytotoxicity and chemical profile from Inga laurina (Fabaceae) - Falcoski, T. O.R. [UNESP]; Lima, N. M. [UNESP]; Navegante, G. [UNESP]; Serafim, R. B. [UNESP]; Sorbo, J. M. [UNESP]; Valente, V. [UNESP]; Santos, V. N.C.; Santos, R. A.; Silva, D. H.S. [UNESP]; Soares, C. P. [UNESP] (Taylor & Francis, 2019)
This study aimed to evaluate the cytotoxicity and genotoxicity from Inga laurina leaves extracts and fractions and obtain their chemical profile. The chemical profile of the crude extract from I. laurina leaves and its fractions was investigated through 1 H NMR, RP-HPLC-PDA by co-injection with authentic standards and HPLC-MS. The quinone reductase induction as a biomarker for cancer chemoprevention was evaluated in murine hepatocellular carcinoma line, whereas the cytotoxicity was evaluated by sulforhodamine B assay (SRB) using HepG2 cell line and genotoxicity was evaluated by comet assay. The phytochemical analysis of the leaves crude extract and its fractions showed the presence of 2-hydroxyethyl-dodecanoate and the phenolic compounds: gallic acid, methyl gallate, p-coumaric acid, cinnamic acid, myricetin-3-O-(2″-O-galoyl)-α-rhamnopyranoside, proanthocyanidin A-2 and myricetrin. All the fractions tested were not considered cytotoxic against the selected human cancer cell lines, they did not cause genotoxic in some concentrations damage and induced the enzyme quinone reductase.
Keywords: cytotoxicity; Fabaceae; genotoxicity; Inga laurina; phenolic compounds